Associations between health behaviors and oral health characteristics with unmet dental care needs among workers: data from the 2025 Korea Community Health Survey - Min-Hee Hong; Jung-Min Lee (Journal of Korean Society of Dental Hygiene, 2026)
Objective: To identify the factors associated with unmet dental care needs among workers, using data from the 2025 Korea Community Health Survey. Methods: This secondary analysis included data from 126,954 workers with valid responses regarding unmet dental care needs. Missing responses for independent variables were excluded from the corresponding analyses. Complex sample frequency analysis, cross-tabulation, and logistic regression analysis were performed. Results: Female workers, smokers, binge drinkers, those who walked minimally, those with high stress, and those who experienced depressive symptoms were more likely to have unmet dental care needs. Among oral health factors, poor subjective oral health, chewing discomfort, and non-participation in oral health examinations were strongly associated with unmet dental care needs. Conclusions: Unmet dental care needs among workers were associated with sociodemographic characteristics, health behaviors, mental health, and oral health factors. Poor subjective oral health, chewing discomfort, and non-participation in oral health examinations were particularly relevant factors. These findings provide basic evidence for the development of workplace-based oral health programs and strategies to improve access to preventive dental services.